The more you value, the less you practice: a study on culture and managerial discretion - Haj Youssef, Moustafa Salman (2020)
Purpose The purpose of this paper is to examine cross-cultural differences in managerial discretion and the extent to which variations and interaction of cultural practices and values affect the degree of freedom in decision making that is accorded to executives. This paper offers a holistic approach to investigating culture in addition to acknowledging its paradoxical nature. Design/methodology/approach Using a panel of prominent management consultants to rate discretion across 18 countries, the authors further develop the national-level construct of managerial discretion by empirically investigating the influence of cultural practices and values on CEOs’ discretion. Findings The study reveals that cultural values moderate the relationship between cultural practices and managerial discretion for three cultural dimensions: individualism, uncertainty tolerance and power distance (PD). By adopting the logic of marginal utility, the authors also show that the more a society values individualism, uncertainty tolerance and PD, the weaker the effect of their practices on managerial discretion. Originality/value Few research has attempted to assess both cultural values and practices in relation to managerial discretion. By showing the mechanism in which culture affects the level of managerial discretion, the authors offer new theoretical insights and practical implications, overall contributing to the field of cross-cultural and strategic management. Finally, this will offer CEO’s a new perspective of leveraging culture as a tool, enhancing their decision-making capabilities in the aim of improving organizational performance.